Study of The Mass Transfer Coefficient from Lignin Removal Process of Coffee Husk in a Baffled Reactor - Nandini, Atika; Edahwati, Luluk (Universitas Pahlawan Tuanku Tambusai, 2024)
The organosolv method of delignification uses organic solvents such as ethanol to remove lignin from biomass. The aims of this research to determine mass transfer coefficient in the delignification process of coffee husk. The White rot fungus, Phanerochaete chrysosporium, was used to degrade lignin component in incubation process of coffee husk biomass, then acid hydrolysis process was carried out by using citric acid to degrade the polysaccharides content (cellulose and hemicellulose). The lignin removal process was conducted at temperature of 50°C, an ethanol concentration of 25%, stirring rates (500-700 rpm) and stirring time (30-180 minutes). The effects of mass transfer were evaluated for variation of stirring rates and stirring time. The results of mass transfer coefficient ranged on 0.0550/s and 0.6710/s. This result indicates an increase in stirring time and stirring rate leads to a higher mass transfer coefficient.